Pengaruh Komunikasi, Komitmen Dan Mentoring Terhadap Peningkatan Kinerja Karyawan (Studi Terhadap Komunitas Jaringan Karyawan Pada Kedai Kopi Malang Raya) - Kurniawan, Luki Fendi; Wahono, Budi; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to study and analyze the impact of communication, participation and mentoring on employee performance. The type of research used is quantitative causality research with a questionnaire data collection method. The Greater Malang coffee shop network community is where this research was conducted. A total of 90 samples were taken in this research, which was aimed at employees at coffee shops in Malang Raya, totaling 90 respondents. The tool used for data processing is SPSS version 26. In this research, it is free from data validity and reliability. Data analysis tests used for this research are normality test, classical assumption test, multiple linear regression analysis, hypothesis testing and also testing the coefficient of determination (R2). The variables used in this research are employee performance (Y), communication (X1), commitment (X2) and mentoring (X3).The results of this research have final results which show that there is a positive impact on communication, commitment and mentoring on improving employee performance. Keywords : Communication, Commitment, Mentoring & Employee Performance